Responses of different strains of saccharomyces cerevisiae to osmotic stress - Noorhisham Tan Kofli,; Keisuke Nagahisa,; Suteaki Shioya, (Universiti Kebangsaan Malaysia, 2006)
During fermentation cells are subjected to various kinds of stress. One of the stresses concerned is high osmotic environment, which cells need to encounter in order to continue growing. To understand how cells adapt to this stress condition, information from genome, proteome and metabolome levels are crucial. In yeast cells, it was report that they produce glycerol to avoid depletion of water in the cell that could lead to cell shrinkage and eventually death. Thus, investigation of physiological responses were executed by shake flask method using three different Saccharomyces cerevisiae strains namely s288c, IFO2347 and FY834 which were grown in yeast potato dextrose (YPD) medium under the treatment of sodium chloride (NaCl) and sorbitol at 1M concentration to create the osmotic condition. These agents were added into the medium after 5 hours of fermentation when the cells reached exponential phase and carbon source is still available. The results proved that addition of both NaCl and sorbitol created the osmotic condition during growth resulted in higher accumulation of glycerol and trehalose when compared to the control in all strains. Among these strains, production of glycerol (g glycerol/g cell dry weight) was found highest in IFO2347, followed by s288c and FY834.